Knowledge, attitude and practice of pregnant women towards prevention of malaria in Itezhi-tezhi, Lusaka, Mazabuka and Monze districts - Bbuku, Naomi; Chipembele, Concepter; Moonga, Catherine; Nkhata, Ruth. (Lusaka: University of Zambia, School of Medicine, 2014)
Malaria can be prevented by using interventions like sleeping under insecticide treated mosquitoe nets, conducting indoor residual spraying. using of intermittent presumptive treatment for pregnant women and keeping the environment free from breeding areas for mosquitoes. The main objective of the study was to determine the knowledge, attitude and practice of pregnant women towards malaria prevetion in Lusaka.
Includes bibliographical references.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Keywords: Malaria in pregnancy--Zambia--Prevention.; Malaria in pregnancy--Treatment--Zambia.